Human Lymph Node-Derived Fibroblastic and Double-Negative Reticular Cells Alter Their Chemokines and Cytokines Expression Profile Following Inflammatory Stimuli - Severino, Patricia; Palomino, Diana Torres; Alvarenga, Heliene; Almeida, Camila Bononi; Pasqualim, Denise Cunha; Cury, Adriano; Salvalaggio, Paolo Rogério; De Vasconcelos Macedo, Antonio Luiz; Andrade, Maria Claudina; Aloia, Thiago; Bromberg, Silvio; Rizzo, Luiz Vicente; et al. (Frontiers in Immunology, 2017)
Lymph node (LN) is a secondary lymphoid organ with highly organized and compartmentalized structure. Lymph nodes harbor B, T, and other cells among which fibroblastic reticular cells (FRCs). FRCs are characterized by both podoplanin (PDPN/gp38) expression and by the lack of CD31 expression. FRCs are involved in several immune response processes but mechanisms underlying their function are still under investigation. Double negative cells (DNCs), another cell population within LNs, are even less understood. They do not express PDPN or CD31, their localization within the LN is unknown and their phenotype and function remain to be elucidated. This study evaluates the gene expression and cytokines and chemokines profile of human LN-derived FRCs and DNCs during homeostasis and following inflammatory stimuli. Cytokines and chemokines secreted by human FRCs and DNCs partially diverged from those identified in murine models that used similar stimulation. Cytokine and chemokine secretion and their receptors expression levels differed between stimulated DNCs and FRCs, with FRCs expressing a broader range of chemokines. Additionally, dendritic cells demonstrated increased migration towards FRCs, possibly due to chemokine-induced chemotaxis since migration was significantly decreased upon neutralization of secreted CCL2 and CCL20. Our study contributes to the understanding of the biology and functions of FRCs and DNCs and, accordingly, of the mechanisms involving them in immune cells activation and migration.